Metode Selimut Insulasi Panas untuk Pencegahan Penurunan Suhu Tubuh Bayi Tikus Putih - Diah Eka Nugraheni; Elvi Destariyani; Sri Sumiati (Jurnal Kesehatan, 2019)
The temperature decrease is caused by heat loss by conduction, convection, evaporation, and radiation. Various methods for preventing heat loss in newborns include the use of plastic bags. Nugraheni's research in 2016, the use of plastic wrap in newborns can still result in body heat loss because polyethylene plastic is not heated insulation. Aluminum foil is one of the ingredients that insulates heat insulation. The use of aluminum foil is widely used in various fields, for example as a food wrap to keep it warm and an emergency blanket for mountain climbers. This study aims to determine the comparison of the use of blanket heat insulation and plastic wrap in preventing the decrease in body temperature of babies of white rats. The type of research used was quasi-experimental (Quasi-Experiment) with the design of "post test only control group design". The sample in this study was 30 white rats which were calculated based on Federer's formula. There were no statistically significant difference in the 15th minute p=0.221, 30th minute p=0.65 and 30th minute p=0.08, this was due to the small number of samples studied but in a systematic way, the control group's median difference was -0.1, then there was no significant difference in temperature change at 15 minutes in the blanket and plastic wrap group. In the 30th minute, the median difference in the control group was -0.5, so clinically there were differences in the blanket group and the plastic wrap group with a median difference of 0.0. In the 60th minute, the median difference in the control group was -1.2, clinically there were differences in the blanket group and the plastic wrap group with a median difference of 1.9. There is a difference in the decrease in body temperature of baby white rats using the blanket method of heat insulation and plastic wrap.